Social interaction reward decreases p38 activation in the nucleus accumbens shell of rats. (December 2015) - Salti, Ahmad; Kummer, Kai K.; Sadangi, Chinmaya; Dechant, Georg; Saria, Alois; El Rawas, Rana
Abstract: We have previously shown that animals acquired robust conditioned place preference (CPP) to either social interaction alone or cocaine alone. Recently it has been reported that drugs of abuse abnormally activated p38, a member of mitogen-activated protein kinase family, in the nucleus accumbens. In this study, we aimed to investigate the expression of the activated form of p38 (pp38) in the nucleus accumbens shell and core of rats expressing either cocaine CPP or social interaction CPP 1 h, 2 h and 24 h after the CPP test. We hypothesized that cocaine CPP will increase pp38 in the nucleus accumbens shell/core as compared to social interaction CPP. Surprisingly, we found that 24 h after social interaction CPP, pp38 neuronal levels were decreased in the nucleus accumbens shell to the level of naïve rats. Control saline rats that received saline in both compartments of the CPP apparatus and cocaine CPP rats showed similar enhanced p38 activation as compared to naïve and social interaction CPP rats. We also found that the percentage of neurons expressing dopaminergic receptor D2R and pp38 was also decreased in the shell of the nucleus accumbens of social interaction CPP rats as compared to controls. Given the emerging role of p38 in stress/anxiety behaviors, these results suggest that (1) social interaction reward has anti-stress effects; (2) cocaine conditioning per se does not affect p38 activation and that (3) marginal stress is sufficient to induce p38 activation in the shell of the nucleus accumbens. Highlights: We investigate pp38 expression in the accumbens after cocaine and social reward. Social reward decreases pp38 neuronal levels in the shell to the level of naïve rats. Cocaine conditioning per se does not affect p38 activation. Marginal stress is sufficient to induce pp38 in the shell of the nucleus accumbens. Social interaction reward may have anti-stress effects.